Age‐associated vascular inflammation promotes monocytosis during atherogenesis. Issue 4 (2nd May 2016) - Du, Wei; Wong, Christine; Song, Yang; Shen, Hua; Mori, Daniel; Rotllan, Noemi; Price, Nathan; Dobrian, Anca D.; Meng, Hailong; Kleinstein, Steven H.; Fernandez‐Hernando, Carlos; Goldstein, Daniel R.
Summary: Aging leads to a proinflammatory state within the vasculature without disease, yet whether this inflammatory state occurs during atherogenesis remains unclear. Here, we examined how aging impacts atherosclerosis using Ldlr −/− mice, an established murine model of atherosclerosis. We found that aged atherosclerotic Ldlr −/− mice exhibited enhanced atherogenesis within the aorta. Aging also led to increased LDL levels, elevated blood pressure on a low‐fat diet, and insulin resistance after a high‐fat diet (HFD). On a HFD, aging increased a monocytosis in the peripheral blood and enhanced macrophage accumulation within the aorta. When we conducted bone marrow transplant experiments, we found that stromal factors contributed to age‐enhanced atherosclerosis. To delineate these stromal factors, we determined that the vasculature exhibited an age‐enhanced inflammatory response consisting of elevated production of CCL‐2, osteopontin, and IL‐6 during atherogenesis. In addition, in vitro cultures showed that aging enhanced the production of osteopontin by vascular smooth muscle cells. Functionally, aged atherosclerotic aortas displayed higher monocyte chemotaxis than young aortas. Hence, our study has revealed that aging induces metabolic dysfunction and enhances vascular inflammation to promote a peripheral monocytosis and macrophage accumulation within the atherosclerotic aorta.